2011
DOI: 10.1080/15421406.2011.569529
|View full text |Cite
|
Sign up to set email alerts
|

Influence ofMeso-Substituted Porphyrins Molecular Structure on Their Self-Organization in Floating Layers

Abstract: The influence of molecular structure peculiarities on the supramolecular organization in the bulk and thin layers was studied by the example of two new mesosubstituted ligands of tetraphenylporphyrin with substitution in alkoxygroups (-OC 4 H 9 ) in para-or ortho-positions of phenyl rings. It is established that mesoalkyloxysubstituted tetraphenylporphyrin with substituents (-OC 4 H 9 ) in the ortho-position (compound I) shows thermotropic monotropic mesomorphism, whereas the substitution in para-position (com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…According to our previous study, [11] these high speeds can lead to the layer fracture and formation of polylayer structures in the floating layers. Thus, we can say that the floating layers of the investigated phthalocyanine derivative are transferred onto the solid substrate preserving their structure (the transfer was carried out from the bilayer containing polylayer formations, the model thickness of Sample No 1 in the bilayer region was about 20 nm, 4 transfers).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…According to our previous study, [11] these high speeds can lead to the layer fracture and formation of polylayer structures in the floating layers. Thus, we can say that the floating layers of the investigated phthalocyanine derivative are transferred onto the solid substrate preserving their structure (the transfer was carried out from the bilayer containing polylayer formations, the model thickness of Sample No 1 in the bilayer region was about 20 nm, 4 transfers).…”
Section: Resultsmentioning
confidence: 88%
“…Based on the simulation data of the supramolecular organization of the mix-substituted phthalocyanine holmium complex in the thin films, [11] and synchrotron study, [12] we can claim that the molecules form a rarefied layer on the water surface under the conditions of Sample No 5 preparation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have shown that organic light emitting diodes (OLEDs) based on Langmuir-Blodgett films have better performance characteristics than OLEDs obtained by other methods [17]. At the same time, the study of floating layers of phthalocyanine derivatives is necessary, since the structure and properties of thin-film materials usually depend on the supramolecular organization of floating layers [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…В отличие от других способов формирования и нанесения тонких пленок они не требуют дорогостоящего оборудования или каких-то специальных условий, что выгодно их отличает от методов, требующих высоких температур, вакуума и пр. Однако, регулируя легко изменяемые факторы во время образования монослоя (например, начальную степень покрытия поверхности, скорость сжатия, температуру), можно добиться существенного различия в его конечных параметрах [20][21][22][23][24][25]. С помощью этих методов формируются плавающие монослои самых различных, в том числе композитных материалов [26][27][28][29][30][31][32].…”
Section: Introductionunclassified